Neurotrophic factors modulation by adenosine receptors and dopamine release in the rat striatum - Gomes, Catarina Alexandra dos Reis Vale, 1976- (2010)
Tese de doutoramento, Ciências Biomédicas (Neurociências), Universidade de Lisboa, Faculdade de Medicina, 2010